2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Defense by Restricting the Hidden Space of Deep Neural Networks

Abstract: Deep neural networks are vulnerable to adversarial attacks, which can fool them by adding minuscule perturbations to the input images. The robustness of existing defenses suffers greatly under white-box attack settings, where an adversary has full knowledge about the network and can iterate several times to find strong perturbations. We observe that the main reason for the existence of such perturbations is the close proximity of different class samples in the learned feature space. This allows model decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 38 publications
0
94
0
Order By: Relevance
“…Reference [32] proposed an efficient approach that bring adversarial samples onto the natural image manifold, restoring classification towards correct classes. Reference [33] maximally separated the polytopes of classes by force to learn distinct and distant decision regions for each classes.…”
Section: B Defense Methodsmentioning
confidence: 99%
“…Reference [32] proposed an efficient approach that bring adversarial samples onto the natural image manifold, restoring classification towards correct classes. Reference [33] maximally separated the polytopes of classes by force to learn distinct and distant decision regions for each classes.…”
Section: B Defense Methodsmentioning
confidence: 99%
“…Adversarial training adds adversarial samples to the training process, helping the model to learn how to deal with an attacker [15,27]. Pang et al use an ensemble of models to increase decision robustness [38], while Mustafa et al use class-wise disentanglement to restrict feature maps crossing the decision boundaries [37]. However, Schott et al showed that even building robust classification on the small MNIST data remains an unsolved problem [41].…”
Section: Related Workmentioning
confidence: 99%
“…There have been several recent papers showing that using metric learning loss functions during training helps in making neural networks more robust to adversarial examples [22][23][24].…”
Section: Our Taxonomymentioning
confidence: 99%
“…Mustafa, et al [23], used their own variation of the contrastive center-loss [25], that encourages both intra-class compactness and inter-class separation of the feature vectors or logits, which are the activations from the last hidden layer. The center loss [26], is a loss function that encourages the feature vectors for each class to lie close to each other (i.e., it encourages intraclass compactness) and the contrastive center-loss function is a generalization of it that also encourages interclass separation.…”
Section: Our Taxonomymentioning
confidence: 99%